Isolation, sequence analysis, and physiological properties of enkephalins in the nervous tissue of the shore crab Carcinus maenas L. - Lüschen, W (1991)
[Leu]- and [Met]enkephalin from thoracic ganglia of the shore crab Carcinus maenas have been purified to homogeneity by a reversed-phase HPLC procedure. Automated gas-phase sequencing revealed a primary structure identical with that of enkephalins from vertebrates. The immunoreactive material in different parts of the nervous system of C. maenas was measured by RIA. Isolated crustacean [Leu]enkephalin shows physiological properties identical to synthetic [Leu]enkephalin in our bioassay. The enkephalinergic effect has been monitored by two bioassays: (i) inhibition of release of crustacean hyperglycemic hormone from isolated eyestalks of C. maenas, and (ii) decreased effect on blood glucose level in the fiddler crab Uca pugilator. The decrease in blood sugar level induced by [Leu]enkephalin was antagonized by naloxone, indicating a receptor-mediated process. In sequence analysis, the thoracic ganglion yielded 3 pmol of [Leu]enkephalin and approximately 1 pmol of [Met]enkephalin. The presence of enkephalins in crustaceans shows an earlier phylogenetic origin of opioids than presumed.